Prospective Evaluation of Acoustic Radiation Force Impulse (ARFI) Elastography and High-Frequency B-Mode Ultrasound in Compensated Patients for the Diagnosis of Liver Fibrosis/Cirrhosis in Comparison to Mini-Laparoscopic Biopsy - Pfeifer, Lukas; Zopf, Steffen; Schwitulla, Judith; Wildner, Dane; Wachter, David; Neurath, Markus; Strobel, Deike; Siebler, Jürgen (Ultraschall in der Medizin, 2015)
Purpose: Ultrasound is a well-established noninvasive test for assessing patients with liver disease. This study aims to prospectively compare ultrasound to the new technique elastography (ARFI) for the assessment of liver fibrosis/cirrhosis. Materials and Methods: High-frequency B-mode ultrasound (liver surface/vein irregularity, liver homogeneity, spleen size), ARFI quantification, mini-laparoscopic liver evaluation including biopsy were prospectively obtained in compensated patients scheduled for liver biopsy. For the diagnosis of cirrhosis, a combined gold standard (cirrhosis at histology and/or at macroscopic liver evaluation) was used. Results: Out of 157 patients, 35 patients were diagnosed cirrhotic. Ultrasound (combination of liver vein and/or surface irregularity) showed no significant difference compared to ARFI quantification for the diagnosis of significant liver fibrosis (Ishak> = 3) and cirrhosis. Diagnosis of cirrhosis had a sensitivity/specificity/PPV/NPV of 83 %(± 12) / 82 %(± 7) / 57 %(± 14) / 94 %(± 4), respectively, with ultrasound and 86 %(± 12) / 81 %(± 7) / 57 %(± 13) / 95 %(± 4), respectively, with ARFI quantification. The sensitivity/specificity/PPV/NPV for the detection of significant fibrosis were 68 %(± 13) / 86 %(± 7) / 71 %(± 13) / 84 %(± 7), respectively, for ultrasound and 70 %(± 12) / 84 %(± 7) / 69 %(± 12) / 84 %(± 7), respectively, for ARFI quantification. Conclusion: ARFI elastography and high-frequency B-mode ultrasound show similar and good results for the diagnosis of compensated liver cirrhosis and high-grade fibrosis. A key benefit of both methods is the high NPV suggesting them as noninvasive exclusion tests.
EVALuna2:2049